Dystonia-Causing Mutations as a Contribution to the Etiology of Spasmodic Dysphonia. (October 2016) - de Gusmão, Claudio M.; Fuchs, Tania; Moses, Andrew; Multhaupt-Buell, Trisha; Song, Phillip C.; Ozelius, Laurie J.; Franco, Ramon A.; Sharma, Nutan
Objective: Spasmodic dysphonia is a focal dystonia of the larynx with heterogeneous manifestations and association with familial risk factors. There are scarce data to allow precise understanding of etiology and pathophysiology. Screening for dystonia-causing genetic mutations has the potential to allow accurate diagnosis, inform about genotype-phenotype correlations, and allow a better understanding of mechanisms of disease. Study Design: Cross-sectional study. Setting: Tertiary academic medical center. Subjects and Methods: We enrolled patients presenting with spasmodic dysphonia to the voice clinic of our academic medical center. Data included demographics, clinical features, family history, and treatments administered. The following genes with disease-causing mutations previously associated with spasmodic dysphonia were screened: TOR1A (DYT1), TUBB4 (DYT4), and THAP1 (DYT6). Results: Eighty-six patients were recruited, comprising 77% females and 23% males. A definite family history of neurologic disorder was present in 15% (13 of 86). Average age (± standard deviation) of symptom onset was 42.1 ± 15.7 years. Most (99%; 85 of 86) were treated with botulinum toxin, and 12% (11 of 86) received oral medications. Genetic screening was negative in all patients for the GAG deletion in TOR1A (DYT1) and in the 5 exons currently associated with disease-causing mutations in TUBB4 (DYT4). Two patients tested positive for novel/rare variants in THAP1 (DYT6). Conclusion: Genetic screening targeted at currently known disease-causing mutations in TOR1A, THAP1, and TUBB4 appears to have low diagnostic yield in sporadic spasmodic dysphonia. In our cohort, only 2 patients tested positive for novel/rare variants in THAP1 . Clinicians should make use of genetic testing judiciously and in cost-effective ways.